(untitled) (Huellas, 2021)
Building risk spaces differ according to the history of the urban development and the environmental context of each city. The aim of this work is to analyze historical-territorial periods that generated the construction of flood risk areas in the city of San Carlos de Bariloche, Río Negro, Argentina. The Dagwood Sandwich methodology was applied to analyze the urbanization and its transformations over time and the role played by the environment and the impacts caused by society. Correlations were observed within six historical-territorial crosscutting moments at different scales (local, provincial, national and international) and the development of exposed spaces to different dangers. This methodology allows identifying and acknowledging the current and historical environmental situation, in order to forecast possible trends of urban expansion and the generation of new flood-risk territories.